P3_3 On the Atmospheric Effects of Cavorite - Middleton, C. J.; Buttery, H. W.; Moore, C. D.Y.; Peck, R. H. (Physics Special Topics, 2016)
We estimate the gravitational and atmospheric effects of a fictional substance known as Cavorite, a material proposed by H.G. Wells that is “opaque to gravitation”. We conclude that for a Cavorite sheet of radius 1 m the impact on the gravitational acceleration is only meaningful at less than 12 m above the plate, and is insignificant at heights greater than this. Therefore, the atmosphere is unlikely to vent away as claimed.